Discrete somatic niches coordinate proliferation and migration of primordial germ cells via Wnt signaling - Cantú, Andrea V. (J Cell Biol, 2016)
Inheritance depends on the expansion of a small number of primordial germ cells (PGCs) in the early embryo. Proliferation of mammalian PGCs is concurrent with their movement through changing microenvironments; however, mechanisms coordinating these conflicting processes remain unclear. Here, we find that PGC proliferation varies by location rather than embryonic age. Ror2 and Wnt5a mutants with mislocalized PGCs corroborate the microenvironmental regulation of the cell cycle, except in the hindgut, where Wnt5a is highly expressed. Molecular and genetic evidence suggests that Wnt5a acts via Ror2 to suppress β-catenin–dependent Wnt signaling in PGCs and limit their proliferation in specific locations, which we validate by overactivating β-catenin in PGCs. Our results suggest that the balance between expansion and movement of migratory PGCs is fine-tuned in different niches by the opposing β-catenin–dependent and Ror2-mediated pathways through Wnt5a. This could serve as a selective mechanism to favor early and efficient migrators with clonal dominance in the ensuing germ cell pool while penalizing stragglers.